Radio and X-ray detections of GX 339–4 in quiescence using MeerKAT and Swift. (6th February 2020) - Tremou, E; Corbel, S; Fender, R P; Woudt, P A; Miller-Jones, J C A; Motta, S E; Heywood, I; Armstrong, R P; Groot, P; Horesh, A; van der Horst, A J; Koerding, E; et al.
ABSTRACT: The radio–X-ray correlation that characterizes accreting black holes at all mass scales – from stellar mass black holes in binary systems to supermassive black holes powering active galactic nuclei – is one of the most important pieces of observational evidence supporting the existence of a connection between the accretion process and the generation of collimated outflows – or jets – in accreting systems. Although recent studies suggest that the correlation extends down to low luminosities, only a handful of stellar mass black holes have been clearly detected, and in general only upper limits (especially at radio wavelengths) can be obtained during quiescence. We recently obtained detections of the black hole X-ray binary (XRB) GX 339–4 in quiescence using the Meer Karoo Array Telescope (MeerKAT) radio telescope and Swift X-ray Telescope instrument on board the Neil Gehrels Swift Observatory, probing the lower end of the radio–X-ray correlation. We present the properties of accretion and of the connected generation of jets in the poorly studied low-accretion rate regime for this canonical black hole XRB system.